Integrasi Sistem Informasi Manajemen dengan Knowledge Management untuk Meningkatkan Pengambilan Keputusan Organisasi - Fitri Dasuki Siregar; Muhammad Irwan Padli Nasution (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
In the dynamic digital era, information and knowledge management becomes a crucial element in improving the effectiveness of organizational decision-making. Integration between Management Information Systems (MIS) and Knowledge Management (KM) is a strategic approach that can strengthen organizational capabilities in responding to internal and external challenges. Management Information Systems function as a tool in collecting, transmitting, and presenting relevant data, while Knowledge Management plays a role in collecting, storing, and distributing knowledge, both explicit and tacit, within the organization. This study aims to examine how the synergy between MIS and KM can improve the quality of managerial decisions, accelerate the flow of information, and support organizational innovation. The methodology used includes literature studies and descriptive analysis of the implementation of MIS-KM in various industrial sectors. The results of the analysis show that organizations that successfully integrate these two systems are able to create a collaborative, adaptive, and responsive knowledge-based work environment to change. In addition, this integration also encourages the alignment of business strategies with available knowledge, resulting in more appropriate and sustainable decisions. Thus, the development of MIS that is closely connected to the KM process is an important need for modern organizations.